Effectiveness of utilizing automatic residential spatial diagraming by senior architectural students - Hoseini, Ali Ghaffarian (2012)
This research is categorized under design computing and cognition while focusing on the way architects think and perform throughout the architectural residential spatial diagramming practices. This research tries to move forward design computing fundamental process through comprehending the design cognition procedure during the spatial planning practices. Architectural spatial planning practices are usually illdefined and over-constrained causing the architectural spatial layout planning as one of the most complicated and challenging stages of the design process. Additionally,CAD development process has majorly focused on preparation of detailed, wellrendered and high end visualization outputs rather than measurement based evaluation outcomes. Therefore, architects have difficulty automatically evaluating the functional efficiency of architectural spatial diagrams during the conceptual design stage. Correspondingly, this research utilizes organizational simulation/evaluation theory to mitigate the aforementioned obstacle. In addition,this study examines the effectiveness of utilizing such systems in order to step forward towards automation of the architectural spatial diagramming. This research highlights the design computing and cognition in terms of assessing the development of an innovative approach for performing the architectural spatial diagramming compared to the conventional method. This research followed a quantitative computational experiment thus; a respective computational prototype has been developed to assist during the automatic visualization and evaluation of architectural spatial diagrams. The research verifies the effectiveness of the innovatively developed process based on implementation of a comparison between the conventional and the proposed process. This research supports March and Simon‘s theory while extending VDT‘s organizational design simulation/evaluation theory hence formalizing graph theoretical evaluation principles to be applied for architectural residential spatial diagramming purposes. Consequently, this research claims the effectiveness of utilizing the developed system compared to the conventional progress.